2021
DOI: 10.1371/journal.pone.0258406
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community-based health education and home support program to reduce blood pressure among patients with uncontrolled hypertension in Nepal: A cluster-randomized trial

Abstract: Background Hypertension is a major global public health problem. Elevated blood pressure can cause cardiovascular and kidney diseases. We assessed the effectiveness of health education sessions and home support programs in reducing blood pressure among patients with uncontrolled hypertension in a suburban community of Nepal. Methods We conducted a community-based, open-level, parallel-group, cluster randomized controlled trial in Birendranagar municipality of Surkhet, Nepal. We randomly assigned four cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…HTN medication was missed due to forgetfulness, negligence, and unaffordability ( 62 ), which could be attributed to a lack of or poor HTN knowledge among community members ( 50 ) and the female community health volunteers (FCHVs) ( 81 ). However, when these cadres were trained and prepared as change agents, the intervention could reduce a mean blood pressure by 2.3–4.9 mm Hg and increase the proportion of BP control and knowledge of the community members ( 70 , 82 ).…”
Section: Resultsmentioning
confidence: 99%
“…HTN medication was missed due to forgetfulness, negligence, and unaffordability ( 62 ), which could be attributed to a lack of or poor HTN knowledge among community members ( 50 ) and the female community health volunteers (FCHVs) ( 81 ). However, when these cadres were trained and prepared as change agents, the intervention could reduce a mean blood pressure by 2.3–4.9 mm Hg and increase the proportion of BP control and knowledge of the community members ( 70 , 82 ).…”
Section: Resultsmentioning
confidence: 99%
“…High blood pressure is a major risk factor for many diseases and the leading cause of death worldwide (23). High blood pressure is a major modifiable risk factor for stroke, cardiovascular disease and renal failure, and disability worldwide (24,25). Because the symptoms of high blood pressure are not known, people do not feel the dangers and do not believe they are at risk (23).…”
Section: Discussionmentioning
confidence: 99%
“…20 Original Article than our findings whereas many studies from other part of Nepal reported prevalence of hypertension more than 30% which is higher than our findings. [12][13][14][24][25][26] These studies however differed in terms of sample size, participant's age, residence and ethnicity. Mean prevalence of hypertension in our study is consistent with the mean prevalence of hypertension found in the different systemic reviews and meta-analysis studies of Nepal (27.3%).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Several studies have shown that prevalence of hypertension is increasing in Nepal. [11][12][13][14] Prevalence and risk factors may vary according to different populations and comparatively fewer studies are conducted among rural population, moreover there was no study conducted in this population to assess prevalence of hypertension and risk factors. Thus our study intended to estimate the prevalence of hypertension and find its risk factors in the rural area of Nepal.…”
Section: Introductionmentioning
confidence: 96%